Associations between fitness, physical activity and mental health in a community sample of young British adolescents: baseline data from the Fit to Study trial. Issue 1 (2nd October 2020) - Wheatley, Catherine; Wassenaar, Thomas; Salvan, Piergiorgio; Beale, Nick; Nichols, Thomas; Dawes, Helen; Johansen-Berg, Heidi
Abstract : Objectives: To examine relationships between fitness, physical activity and psychosocial problems among English secondary school pupils and to explore how components of physically active lifestyles are associated with mental health and well-being. Methods: A total of 7385 participants aged 11–13 took a fitness test and completed self-reported measures of physical activity, attitudes to activity, psychosocial problems and self-esteem during the Fit to Study trial. Multilevel regression, which modelled school-level cluster effects, estimated relationships between activity, fitness and psychosocial problems; canonical correlation analysis (CCA) explored modes of covariation between active lifestyle and mental health variables. Models were adjusted for covariates of sex, free school meal status, age, and time and location of assessments. Results: Higher fitness was linked with fewer internalising problems (β=−0.23; 95% CI −0.26 to −0.21; p<0.001). More activity was also related to fewer internalising symptoms (β=−0.24; 95% CI −0.27 to −0.20; p<0.001); the relationship between activity and internalising problems was significantly stronger for boys than for girls. Fitness and activity were also favourably related to externalising symptoms, with smaller effect sizes. One significant CCA mode, with a canonical correlation of 0.52 (p=0.001), was characterised high cross-loadings for positive attitudes to activity (0.46) and habitual activity (0.42) among lifestyle variables; and for physical and global self-esteem (0.47 and 0.42) among mental health variables. Conclusion: Model-based and data-driven analysis methods indicate fitness as well as physical activity are linked to adolescent mental health. If effect direction is established, fitness monitoring could complement physical activity measurement when tracking public health.